MILITARY STRATEGIC AND OPERATIONAL ART OF MASTER AMIR TEMUR - Raкhmanberdyiev Sherzod Suyunbaevich (American Journals, 2023)
The article describes Amir Temur’s military strategy, operations and tactics, which he used in his military art to found a great state in the field of history, as well as the enormous potential, skills, knowledge and experience of the founders.
Keywords: Strategy, war, palace, dungeon, caravan, ruin, ruler, defense, trench, fortress, tower.